Judicial Practice on Official Malfeasance in the Novgorod Province in the 18th Century - MITINA, Svetlana Igorevna; SINKEVICH, Nikolay Alexandrovich; OGORODNIKOV, Vladimir Ivanovich; ROZHKOVA, Irina Yurievna; LUKANIN, Victor Viktorovich (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019, 2020)
The research reveals the problem of the realization of officials’ legal responsibility for mercenary abuses in the service during the period of reforms of public administration in Russia in the 18 th century on the example of the Novgorod province. The general trends and features of the formation of anti-corruption institutions in the system of provincial authorities and the country as a whole are determined based on the analysis of the history of Russian legislation and the study of the materials of judicial practice.